Open access to knowledge: a new right created by globalization - Hernando Gaitán-Duarte (Federación Colombiana de Obstetricia y Ginecología, 2015)
It emerges from the blurring of borders between countries, less independent control of the State over its citizens (1), and shorter effective time between an event occurring and news of it traveling around the world people (2). There are several reasons that explain the emergence of this paradigm: technological developments like the World Wide Web that has given rise to social media such as Facebook, by no means subject to physical borders; immediate access to information either through traditional media like television or press, or through new media like Twitter or YouTube (we all have a clear recall of the live broadcast on television of the attack against the Twin Towers); and, finally, the creation of supranational agencies charged with the role of ensuring respect for human rights, as is the case of the International Criminal Court (ICC) (3). Some authors explain that globalization originates in the prevalent economic tenets of the day: capitalism and the market economy. The idea is to have increasingly larger markets for the consumption of goods and services and to diminish control over international money transactions and investments (4). Hence the talk about global companies like The Coca-cola Company, free trade agreements, and capital flows between countries (1). In this new scenario, weak economies are subjected to pressures imposed by transnational companies or their representatives (5). Added to economic consequences, there are social effects like impacts on workers and population migrations unseen in the recent past, as is the case of crowds fleeing to Europe from places like Syria and North Africa.